PELAKSANAAN SUPERVISI AKADEMIK SEBAGAI STRATEGI PENGEMBANGAN KETERAMPILAN GURU DALAM IMPLEMENTASI PEMBELAJARAN KOLABORATIF DI SEKOLAH DASAR - Ahsanul Huda Susanto; Sutama; Achmad Fathoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study explores the impact of academic supervision conducted by school principals on teachers' skills in designing and implementing collaborative learning at SD Negeri 03 Wukirsawit. The research employed a descriptive qualitative approach. The results of the analysis indicate that scheduled academic supervision using various techniques such as direct observation, interviews, document analysis, and group discussions has a significant positive impact. Teachers successfully implemented collaborative learning effectively after receiving guidance from the school principal, enhancing student engagement and learning outcomes. The school principal plays a key role in creating a supportive educational environment, collaborating with teachers, and fostering open communication. This study contributes to understanding effective academic supervision practices in the context of primary schools and their practical implications for teacher professional development and improving learning quality.